Drug delivery system of dual-responsive PF127 hydrogel with polysaccharide-based nano-conjugate for textile-based transdermal therapy. (15th May 2020) - Chatterjee, Sudipta; Hui, Patrick Chi-leung; Wat, Elaine; Kan, Chi-wai; Leung, Ping-Chung; Wang, Wenyi
Graphical abstract: Highlights: Dual-responsive hydrogel drug delivery system of pluronic F127 and nano-conjugate. Gallic acid loaded as active maker of traditional Chinese medicine Cortex Moutan. pH-responsive nano-conjugate made of hyaluronic acid and chitosan oligosaccharide. Morphology, physico-chemical, and drug release properties of the hydrogel studied. Skin pH condition applied to see the effect on stability and drug release property. Abstract: Pluronic F-127 based dual-responsive (pH/temperature) hydrogel drug delivery system was developed involving polysaccharide-based nano-conjugate of hyaluronic acid and chitosan oligosaccharide lactate and applied for loading of gallic acid which is the principal component of traditional Chinese medicine Cortex Moutan recommended in the treatment of atopic dermatitis. The polysaccharide-based nano-conjugate was used as pH-responsive compound in the formulation and its amphiphilic character was determined colorimetrically. Microstructure analysis by SEM and TEM indicated highly porous hydrogel network and well-dispersed micellar structures, respectively, after modification with the nano-conjugate, and so, release property of the hydrogel for drug was significantly improved. Different pH-conditions were applied here to see pH-responsiveness of the formulation and increase in acidity of external environment gradually diminished mechanical stability of the hydrogel and that was reflected on the drug release property. Rheology was performed to observe sol-gel transition of the formulation and showed better rheological properties after modification with nano-conjugate. In this study, the cytotoxicity results of PF127 based formulations loaded with/without gallic acid showed cell viability of > 80.0 % for human HaCaT keratinocytes in the concentration range of 0.0–20.0 μg/ml.